Can guidance during play enhance children's learning and development in educational contexts? A systematic review and meta‐analysis. Issue 4 (12th January 2022) - Skene, Kayleigh; O'Farrelly, Christine M.; Byrne, Elizabeth M.; Kirby, Natalie; Stevens, Eloise C.; Ramchandani, Paul G.
Abstract: This systematic review and meta‐analysis considered evidence of guided play compared to direct instruction or free play to support children's learning and development. Interventions from 39 studies were reviewed (published 1977–2020); 17 were included in meta‐analysis ( N total = 3893; M childage = 1–8 years; M girls 49.8%; M ethnicity White 41%, African American/Black 28%, Hispanic 19%). Guided play had a greater positive effect than direct instruction on early maths skills ( g = 0.24), shape knowledge ( g = 0.63), and task switching ( g = 0.40); and than free play on spatial vocabulary ( g = 0.93). Differences were not identified for other key outcomes. Narrative synthesis highlighted heterogeneity in the conceptualization and implementation of guided play across studies.